?EFFECT OF CHROMATE, NITRITE AND BENZOATE IONS ADDITIVES ON THE CORROSION BEHAVIOUR OF LOW CARBON STEEL IN ACID MEDIUM (Biological Sciences - PJSIR, 1994)
The effect of CrO"4'N02 and C6HsCOO ions on the inhibitive behaviour of low carbon steel electrodes in aqueous solutions of mono-, di-and tri-chloroacetic acids at pH 1to 4 is calculated by studying potential-time variation, weight loss measurements and galvanostatic polarisation, It has been found that the steady state potentials which obey the re- lationship E = a -b log C, where (a) is aproportional constant and (b) is the order of the reaction which can be obtained from the linear plot of log C versus log corrosion rate which depend on the type of the acids and C is the molar concentration of the acids, is shifted towards less negative values with the increase in the concentration of additive ions and from pH 1 to 2 and then increases again at pH = 3 to 4. The decrease in the rate of corrosion with increase of anion concentration is probably due to the fact that additive ions act as anodic inhibitors. The critical current density for passivation varies with the nature and concentration of the additive anion.